Validitas Lembar Kerja Peserta Didik Berbasis Problem Based Learning Terintegrasi Nilai Preventif Kesehatan Organ Ekskresi pada Materi Sistem Eskresi untuk Fase F SMA: Penelitian - Mutia Yolanda; Rahmadhani Fitri; Muhyiatul Fadilah; Ria Anggriyani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to produce Problem Based Learning-based Learner Worksheets integrated with the preventive value of excretory organ health on excretory system material for Phase F SMA. This research is a type of development research (R&D) that adapts the 4D model from Thiagarajan, namely the defining, designing, and developing stages. The research was conducted at the Department of Biology FMIPA Padang State University and SMAN 1 Payakumbuh District. Data collection instruments consisted of teacher interview sheets, student observation questionnaires, and validity test questionnaires. Validation was carried out by two lecturers of Biology FMIPA UNP and one Biology teacher of SMAN 1 Payakumbuh District. The validated aspects include content eligibility, language, presentation, and graphics. The validation results showed that the LKPD obtained an average score of 3.74 with a very valid category. Therefore, the LKPD developed is declared valid and feasible to use in the biology learning process, especially on the material of the excretory system which emphasizes the application of preventive health values through a problem-based approach.